1990
DOI: 10.1073/pnas.87.19.7787
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-receptor fusion of the human immunodeficiency virus type 1 Rev transactivator: mapping cryptic functions of the arginine-rich motif.

Abstract: The human immunodeficiency virus type 1 (HIV-1) transactivator Rev is a nuclear protein that regulates expression of certain HIV-1 transcripts by binding to an RNA target element (the RRIE) present in these transcripts. A short arginine-rich sequence in Rev contains the signals required to direct this protein into nuclei, where it associates preferentially with nucleoli. We created a steroid-inducible transactivator by fusing Rev with the steroid-binding domain of the glucocorticoid receptor (GR). This Rev/GR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
273
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(282 citation statements)
references
References 29 publications
9
273
0
Order By: Relevance
“…The CTE identified in DR2 of the PrC strain of ASV was previously localized to between nt 8770 and 8925 (Ogert et al+, 1996)+ To confirm that a functional CTE is also present in the ALV, which contain only a single DR, we subcloned the equivalent sequence from a previously described RAV-2 ALV isolate (Bizub et al+, 1984) into the indicator construct pDM128/PL (Fridell et al+, 1993)+ This 159-bp sequence extends 3 bp 39 and 156 bp 59 to the 59 boundary of the ALV LTR and is 68% identical to the equivalent DR2 sequence in the PrC strain of ASV+ As previously described (Hope et al+, 1990), the pDM128 indicator plasmid contains a 59 and a 39 splice site, derived from the HIV-1 env gene, flanking an intronic cat indicator gene+ pDM128/PL additionally contains a polylinker between the cat gene and the 39 splice site, thus permitting the introduction of sequences of interest, such as the ALV CTE or, as previously described, the MPMV CTE or the HIV-1 RRE (Fridell et al+, 1993;Bogerd et al+, 1998)+ Because the cat gene is located between functional 59 and 39 splice sites, CAT enzyme expression is dependent on the nuclear export and translation of an unspliced mRNA, a process that, for the reasons described above, is normally very inefficient+ However, the introduction of an active CTE or of the HIV-1 RRE in cis (in the latter case in the presence of Rev) results in the efficient nuclear export of this unspliced mRNA and, hence, in a marked induction in CAT expression+ We therefore asked whether introduction of the putative ALV CTE would exert a similar effect+ Initially, we transfected the quail cell line QCl-3, which is permissive for RAV-2 replication (Cullen et al+, 1983), FIGURE 1. Schematic representation of the genomic organization of ALV and ASV+ The ASVs, such as Rous Sarcoma Virus, arose because of the recombinational acquisition of the host-cell-derived src gene by ALVs+ This resulted in a duplication of the 39 noncoding sequence located between the env gene and the LTR in the ALVs and this duplicated sequence was hence referred to as the direct repeat+ SD: splice donor; SA: splice acceptor+ with the parental pDM128/PL construct, with derivatives containing the ALV CTE sequence in the sense or anti-sense orientation, or with a pDM128/PL derivative containing the MPMV CTE+ As shown in Figure 2, the sense orientation ALV CTE potently activated CAT expression from the pDM128 indicator plasmid, whereas the same ALV sequence in the anti-sense orientation had no detectable effect+ As previously described , the MPMV CTE is not active in quail cells and the pDM128 construct containing this CTE was therefore also essentially inactive+ Whereas the MPMV CTE is active in human but not quail cells, the PrC ASV CTE was initially reported to be active in avian cells but not primate cells (Ogert et al+, 1996)+ To examine the species tropism of the ALV CTE, we compared the activity of these same four indicator plasmids upon transfection into the human cell line 293T, the simian cell line COS, or the murine L cell line+ As may be observed (Fig+ 2), both the ALV CTE and the MPMV CTE proved to be equivalently active in all three of these distinct cell types+ Therefore, based on this limited analysis, the ALV CTE does not display any obvious species tropism+ In fact, recent unpublished experiments utilizing the PrC ASV CTE demonstrate that this CTE is also active in hu...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CTE identified in DR2 of the PrC strain of ASV was previously localized to between nt 8770 and 8925 (Ogert et al+, 1996)+ To confirm that a functional CTE is also present in the ALV, which contain only a single DR, we subcloned the equivalent sequence from a previously described RAV-2 ALV isolate (Bizub et al+, 1984) into the indicator construct pDM128/PL (Fridell et al+, 1993)+ This 159-bp sequence extends 3 bp 39 and 156 bp 59 to the 59 boundary of the ALV LTR and is 68% identical to the equivalent DR2 sequence in the PrC strain of ASV+ As previously described (Hope et al+, 1990), the pDM128 indicator plasmid contains a 59 and a 39 splice site, derived from the HIV-1 env gene, flanking an intronic cat indicator gene+ pDM128/PL additionally contains a polylinker between the cat gene and the 39 splice site, thus permitting the introduction of sequences of interest, such as the ALV CTE or, as previously described, the MPMV CTE or the HIV-1 RRE (Fridell et al+, 1993;Bogerd et al+, 1998)+ Because the cat gene is located between functional 59 and 39 splice sites, CAT enzyme expression is dependent on the nuclear export and translation of an unspliced mRNA, a process that, for the reasons described above, is normally very inefficient+ However, the introduction of an active CTE or of the HIV-1 RRE in cis (in the latter case in the presence of Rev) results in the efficient nuclear export of this unspliced mRNA and, hence, in a marked induction in CAT expression+ We therefore asked whether introduction of the putative ALV CTE would exert a similar effect+ Initially, we transfected the quail cell line QCl-3, which is permissive for RAV-2 replication (Cullen et al+, 1983), FIGURE 1. Schematic representation of the genomic organization of ALV and ASV+ The ASVs, such as Rous Sarcoma Virus, arose because of the recombinational acquisition of the host-cell-derived src gene by ALVs+ This resulted in a duplication of the 39 noncoding sequence located between the env gene and the LTR in the ALVs and this duplicated sequence was hence referred to as the direct repeat+ SD: splice donor; SA: splice acceptor+ with the parental pDM128/PL construct, with derivatives containing the ALV CTE sequence in the sense or anti-sense orientation, or with a pDM128/PL derivative containing the MPMV CTE+ As shown in Figure 2, the sense orientation ALV CTE potently activated CAT expression from the pDM128 indicator plasmid, whereas the same ALV sequence in the anti-sense orientation had no detectable effect+ As previously described , the MPMV CTE is not active in quail cells and the pDM128 construct containing this CTE was therefore also essentially inactive+ Whereas the MPMV CTE is active in human but not quail cells, the PrC ASV CTE was initially reported to be active in avian cells but not primate cells (Ogert et al+, 1996)+ To examine the species tropism of the ALV CTE, we compared the activity of these same four indicator plasmids upon transfection into the human cell line 293T, the simian cell line COS, or the murine L cell line+ As may be observed (Fig+ 2), both the ALV CTE and the MPMV CTE proved to be equivalently active in all three of these distinct cell types+ Therefore, based on this limited analysis, the ALV CTE does not display any obvious species tropism+ In fact, recent unpublished experiments utilizing the PrC ASV CTE demonstrate that this CTE is also active in hu...…”
Section: Resultsmentioning
confidence: 99%
“…The following expression plasmids have been previously described: the mammalian expression plasmids pBC12/CMV, pBC12/CMV/⌬CAN, pBC12/CMV/b-Gal, and pcRev (Malim et al+, 1991;Bogerd et al+, 1998); a derivative of the pDM128/ CMV indicator plasmid containing an intronic polylinker (pDM128/PL) (Hope et al+, 1990;Fridell et al+, 1993); and derivatives containing the full-length HIV-1 RRE or MPMV CTE (Bogerd et al+, 1998)+ The 159-bp, full-length ALV CTE, as well as truncated derivatives, were PCR amplified from a RAV-2 ALV isolate (Bizub et al+, 1984) and inserted into pDM128/PL at the polylinker Bgl II and KpnI sites to generate pDM128/ALV-CTE and the pDM128/SLIϩII, pDM128SLIIϩIII and pDM128/SLII constructs+ Point mutations of the ALV CTE were generated by using the QuickChange site-directed mutagenesis kit (Stratagene) on the parental pDM128/ALV-CTE construct+ The SLII fragment of the ALV CTE was PCR amplified and inserted into pDM128/SLII at the KpnI site to generate pDM128/2XSLII+ A pBluescript/SLII construct was cut with XbaI and ClaI, and the resultant SLII DNA fragment was inserted into pDM128/2XSLII to generate pDM128/3XSLII+ The pBluescript/ALV-CTE plasmid was constructed by inserting the full-length ALV CTE into the BamHI site of the polylinker region+ All constructs were sequenced to verify the correct orientation and sequence+…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…3A) (33). Transcripts produced by pDM128 contain a single intron containing the HIV-1 RRE and the CAT coding sequence, which is excised when it is spliced (33). Cells transfected with pDM128 alone express only spliced transcripts and yield minimal levels of CAT activity; however, when Rev is cotransfected with pDM128, high levels of CAT enzyme are expressed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test this hypothesis, the SF2͞ASF cDNA was cloned into the pCMV4 eukaryotic expression plasmid and cotransfected into CV1 cells together with the pcRev and the Rev-dependent CAT-reporter plasmid pDM128 derived from the env region of HIV (Fig. 3A) (33). Transcripts produced by pDM128 contain a single intron containing the HIV-1 RRE and the CAT coding sequence, which is excised when it is spliced (33).…”
Section: Resultsmentioning
confidence: 99%
“…27,28 Binding of a functional ligand leads to an alteration in the structure of the HBD, which allows release of the chimera from hsp90, refolding to an active form and stabilization by dimerization of the HBD. 28,29 Several intracellular proteins have been rendered functionally hormone-dependent by fusing them with steroid receptors, among them are several viral and cellular transcription factors like E1A, 26,30 HIV Rev, 31 c-Myc 32 and v-Myb. 33 Previously it has been shown that fusion proteins of a mutated HBD of murine estrogen receptor (Mer) 34 or its human analogue (ER) 35 enable very tight regulation of the corresponding effector proteins in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%